2017
DOI: 10.1016/j.cortex.2016.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Unity and diversity of executive functions: Individual differences as a window on cognitive structure

Abstract: Executive functions (EFs) are high-level cognitive processes, often associated with the frontal lobes, that control lower level processes in the service of goal-directed behavior. They include abilities such as response inhibition, interference control, working memory updating, and set shifting. EFs show a general pattern of shared but distinct functions, a pattern described as “unity and diversity.” We review studies of EF unity and diversity at the behavioral and genetic levels, focusing on studies of normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

71
1,350
4
44

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,364 publications
(1,469 citation statements)
references
References 152 publications
(238 reference statements)
71
1,350
4
44
Order By: Relevance
“…This is where a supervisory process called executive function comes into play [23]. These ties in with our ability not only to focus our attention on specific things but also to divide our attention between competing tasks when required to do so.…”
Section: Discussionmentioning
confidence: 99%
“…This is where a supervisory process called executive function comes into play [23]. These ties in with our ability not only to focus our attention on specific things but also to divide our attention between competing tasks when required to do so.…”
Section: Discussionmentioning
confidence: 99%
“…The authors argue that preventing irrelevant information from entering working memory is particularly important when learners have to cope with information in addition to a text comprehension task (Borella & Ribaupierre, 2014). Executive functions appear to be substantially correlated but also have a unique variance (Friedman & Miyake, 2017). This unique variance of the different executive functions may explain why working memory and shifting can be simultaneously and uniquely related to complex academic achievements such as reading abilities (e.g., Jacobson et al, 2016).…”
Section: Approaches To Improve Executive Functionsmentioning
confidence: 99%
“…Executive functions are basic cognitive functions (Andersson, 2010) and as such are typically conceived as effective across domains (Friedman & Miyake, 2017). Executive functions receive attention due to their strong relation to self-control (also referred to as self-regulation) (Miyake & Friedman, 2012).…”
Section: Definition Of Executive Functionsmentioning
confidence: 99%
“…Performance in EM has been traditionally related to intact medial temporal lobe (MTL) structures, whereby the hippocampus orchestrates learning and retrieval in conjunction with the entorhinal, perirhinal, and parahippocampal cortices (Dickerson & Eichenbaum, 2010). By contrast, EFs largely rely on the integrity of prefrontal and other frontal regions, and to some extent of parietal cortex (Friedman & Miyake, 2017; Gläscher et al, 2009). Earlier seminal works conducted on patients with focal brain lesions showed that EM and EFs, although functionally related, are in part behaviorally dissociable, that is, patients with selective MTL damage display EFs within normal psychometric ranges (Augustinack et al, 2014; Buckner, 2004; McKenna & Gerhand, 2002; Rosenbaum et al, 2005), while patients suffering from prefrontal insult demonstrate relatively preserved aspects of EM, especially in recognition memory (Milner, Corsi, & Leonard, 1991; Shimamura, Janowsky, & Squire, 1990; Wheeler & Stuss, 2003).…”
Section: Introductionmentioning
confidence: 99%